Lack of chemoprevention of dietary Agaricus blazei against rat colonic aberrant crypt foci - Ziliotto, L. [UNESP]; Barbisan, Luis Fernando [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP] (Sage Publications Ltd, 2008)
The mushroom Agaricus blazei (Ab) has been widely used in folk medicine to treat various diseases including cancer. No information is available on its possible protective effects on the development of colon cancer. The potential blocking effect of Ab intake on the initiation stage of colon carcinogenesis was investigated in a short-term (4-week) bioassay using aberrant crypt foci (ACF) as biomarker. Male Wistar rats were given four subcutaneous injections of the carcinogen 1,2-dimethylhydrazine (DMH, 40 mg/kg bw, twice a week), during 2 weeks to induce ACK The diet containing Ab at 5% was given 2 weeks before and during carcinogen treatment to investigate the potential beneficial effects of this edible mushroom on DMH-induced ACF. All groups were killed at the end of the fourth week. The colons were analyzed for ACF formation in 1% methylene blue whole-mount preparations and for cell proliferation in histological sections immunohistochemically stained for the proliferating cell nuclear antigen (PCNA). All DMH-treated rats developed ACF mainly in the middle and distal colon. Agaricus blazei intake at 5% did not alter the number of ACF induced by DMH or the PCNA indices in the colonic mucosa. Thus, the results of the present study did not confirm a chemopreventive activity of Ab on the initiation stage of rat colon carcinogenesis.
Keywords: aberrant crypt foci; Agaricus blazei; blocking agents; chemoprevention; colon carcinogenesis; dimethylhydrazine